(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article scientifically analyzes the ways and forms of overcoming negative phenomena in the understanding of national identity. On a global scale, political, geopolitical, economic and cultural processes automatically involve each person in one or another system of information flows. As a result, a person has to live and work in an environment of multi-information exchange, which requires significant changes in spiritual characteristics.